Source code provisions and evolving exceptions in economic agreements - HSU, Locknie (Institutional Knowledge at Singapore Management University, 2025)
This article examines the objectives and constraints of treaty provisions relating to source code disclosure requirements in recent treaties such as free trade agreements and Digital Economy Partnership Agreements. It examines such provisions and in particular, their evolving exceptions, against the tide of technological advancements in artificial intelligence, such as those in Generative AI, as regulators grapple with both the regulation and promotion of such technologies. It raises some key considerations for the negotiation of future provisions and associated exceptions for trade negotiators and legal advisers.